At the grassroots of home and community-based aged care: strategies for successful consumer engagement - Andrew Georgiou; Johanna Westbrook; Joyce Siette; Amy Nguyen; Lindsey Brett; Mikaela Jorgensen; Melissa Miao; Winifred Lee; Edwina Gow; Fleur Hourihan (BMJ Open)
Objectives (1) To describe the processes used to plan and conduct a stakeholder forum in aged care as a means of informing future uptake of consumer participatory research. (2) To discuss how capturing and drawing on stakeholders’ experiences of aged care can generate new research ideas and inform the delivery of more person-centred aged care services.Key principles of consumer engagement A stakeholder forum was conducted as part of Ageing Well, a 2-year project evaluating the value and impact of social participation and quality of life tools as part of routine community aged care assessments at a large Australian provider. The forum was codesigned with community aged care clients and care coordinators and aimed to coproduce implementation strategies with a targeted representation of stakeholders. The stakeholder forum was developed using five key principles of consumer engagement activities: purposeful, inclusive, timely, transparent and respectful. The forum fostered an environment of mutual respect and collective inquiry to encourage contributions from all participants. This article outlines practical guidance on using a consumer engagement framework and the lessons learnt.Discussion The stakeholder forum facilitated an understanding of consumers’ needs and existing gaps in aged care services and the circumstances that can enable or hinder the delivery and implementation of these services. This collective information can guide future research and policy at institutional, regional and national committees that relate to aged care.Trial registration number ACTRN12617001212347